Economic Development Plan in the Subosukowonosraten Area - Nahri, Putri Wulan; Aprisal, Veni (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the economic development plan of the Subosukowonosraten area, which includes Surakarta, Boyolali, Sukoharjo, Wonogiri, Karanganyar, Sragen, and Klaten. As one of the main growth centers in Central Java, this region has strategic potential in agriculture, industry, and services. However, significant challenges remain, particularly in regional disparities caused by differences in economic structures and access to resources. This research employs a qualitative descriptive method complemented by secondary statistical data, such as Gross Regional Domestic Product (GRDP), Williamson Index, and unemployment rate, to capture both the dynamics and inequalities across districts. Analytical tools including Klassen Typology, Location Quotient (LQ), and Shift Share (SS) were applied to identify potential sectors and regional disparities. The findings highlight that the manufacturing industry is the leading contributor to regional GRDP, followed by agriculture, which still faces issues of low productivity and limited competitiveness. To address these challenges, the cluster development approach is proposed as a comprehensive strategy by grouping regions according to their sectoral advantages—industrial, agricultural, or commercial clusters. This method fosters synergy, enhances competitiveness, and ensures sustainable growth through integrated regional cooperation. The proposed plan also emphasizes strengthening agricultural networks, improving human resource capacity through training, and fostering collaboration between government, industry, and educational institutions. Ultimately, the economic development plan of Subosukowonosraten aims to achieve inclusive and equitable growth, reduce disparities, and strengthen the region’s position as a competitive economic hub in Central Java.